A Framework of Hybrid System Dynamics and Agent Based Model With Cooperative Game Theory for Sustainable Coffee Supply Chain - Kamal, M Arif; Santoso, Imam; Effendi, Usman; Astuti, Retno; Mulyarto, Aunur Rofiq; Hidayat, Arif; Effendi, Mas’ud (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The global coffee supply chain is a complex network involving diverse stakeholders such as farmers, traders, exporters, and consumers, each with unique incentives and constraints. This study introduces a conceptual framework that integrates System Dynamics (SD), Agent-Based Modelling (ABM), and Cooperative Game Theory (CGT) to address challenges in profit allocation, coalition stability, and sustainability. SD provides macro-level insights into global trends such as price fluctuations and production dynamics, while ABM models individual decision-making processes. CGT complements these methods by facilitating fair payoff distribution and stable coalition formation. The framework is structured into problem identification, model development and mapping, and interaction mode selection, offering a comprehensive approach to understanding material, information, and decision flows. Using illustrative scenarios, the study demonstrates the framework’s potential to analyses trade-offs and long-term impacts on supply chain stability. Its practical implications could support policymakers and industry leaders in designing fair profit-sharing mechanisms, promoting stable cooperation among stakeholders, and enhancing the overall sustainability of coffee and other agri-food supply chains. Thus, the framework highlights its applicability as a conceptual tool for supporting decision-making and sustainability in coffee supply chains and beyond.